Pengaruh Kompetensi Kepala Sekolah dan Peran Serta Masyarakat Terhadap Mutu Sekolah Dasar Negeri di Kecamatan Ngaliyan Kota Semarang - Khusnawati, Arifah; Kusumaningsih, Widya; Miyono, Noor (PGRI Kota Semarang, 2024)
The competence of the school principal greatly influences the quality of the school because the principal is the leader in the school, whose job is to provide guidance, supervision, and improve the abilities of educational staff. The aims of this research are: (1) to determine the magnitude of the influence of the principal's competence on school quality, (2) to determine the magnitude of the influence of community participation on school quality, and (3) to determine the magnitude of the influence of principal's competence and community participation on school quality. The research approach used is quantitative. This type of research uses correlation research. The population of this study was 377 teachers and the research sample was 194 teachers. Data collection was carried out using a questionnaire. The data analysis technique used in this research is descriptive data analysis, prerequisite tests which include normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests and hypothesis tests including simple and multiple linear regression. The research results show that: (1) The correlation between principal competence and school quality is 0.851. The influence of the principal's competence partially has a significant effect on the school quality variable by 72.4%. (2) The correlation between community participation and school quality is 0.918. The influence of community participation partially has a significant effect on the school quality variable by 84.4%. (3) There is a significant influence of the principal's competence and community participation on school quality with the equation Ŷ = 4.235 + 0.057 X1 + 0.569 X2. Then the correlation coefficient value r is 0.918. The coefficient of determination of the influence of variables X1 and X2 on Y is 84.5%. The conclusion of this research is that there is a significant influence of the principal's competence and community participation on school quality, amounting to 84.5%. The author suggests that school principals can reflect and evaluate by increasing the intensity of supervision. School principals can carry out copy studies from other schools to develop the principal's competence and open themselves to receiving criticism and input in order to improve the quality of the school.